1982
DOI: 10.1002/1097-4679(198210)38:4<703::aid-jclp2270380404>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Coronary risk factor intervention: Characteristics associated with change

Abstract: Predicting change in coronary heart disease (CHD) risk factors (cigarette smoking, hypertension, and cholesterol) was undertaken in participants randomized to the treatment group of the Harvard Center of the Multiple Risk Factor Intervention Trial. The predictor variables of interest were psychosocial characteristics, responses to the initial group sessions intervention strategy, and change in weight. The Harvard sample consists of 652 men identified at high risk of death from CHD. Fifty percent were randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Preillness psychological adjustment has been related to smoking cessation in medical patients (Burns, 1969; Dudley et al, 1977; Eaker, Benfari, & Reed, 1982; Lloyd & Crawley, 1980). In our study, however, only lower levels of preinfarction marital conflicts were related to short-term quitting.…”
Section: Discussionmentioning
confidence: 99%
“…Preillness psychological adjustment has been related to smoking cessation in medical patients (Burns, 1969; Dudley et al, 1977; Eaker, Benfari, & Reed, 1982; Lloyd & Crawley, 1980). In our study, however, only lower levels of preinfarction marital conflicts were related to short-term quitting.…”
Section: Discussionmentioning
confidence: 99%
“…11 Failure to adhere to treatment regimens has been a significant and long-standing problem in healthcare. 12 Over the years, many books and articles have been written on the complex issue of behavioral regimen adherence. 11 One approach to adherence, often called behavioral analysis, focuses on the individual, his or her interactions with the environment, and how the environment affects one's well-being.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…One of the primary premises of Social Learning Theory is that behavior is not simply a product of personal and environmental influences, but that instead the components interact as mutual determinants of each other. 12 For the purpose of this review, the operational definition of behavioral analysis will be as follows: the process by which behavior is observed, documented, and analyzed. Behavior is usually analyzed from 3 perspectives: the antecedent events that precede and serve as stimuli for the behavior, components of the actual behavior, and consequences that follow the behavior.…”
Section: Behavioral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Several independent studies have concluded that for cardiovascular patients, social support is an important determinant in successful attempts at smoking cessation (Eaker, Benfari, & Reed, 1982; Giannetti, Reynolds, & Rihn, 1985;Powell & Arnold, 1982; Sirota, Curran, & Habif, 1985), weight loss (Finnegan & Suler, 1985), and maintenance of exercise programs (Daltroy & Godin, 1989). Highlighting the importance of social support, Marmot (1983) and Carmody, Istvan, Matarazzo, and Connor (1986) stressed the need for involving the family unit as a mechanism for implementing specific guidance and advice in the promotion of healthy-heart diets.…”
mentioning
confidence: 99%